Uric acid is a risk factor for ischemic stroke and all-cause mortality in the general population: a gender specific analysis from The Tromsø Study - Storhaug, Hilde-Merete; Norvik, Jon Viljar; Toft, Ingrid; Eriksen, Bjørn Odvar; Løchen, Maja-Lisa; Zykova, Svetlana; Solbu, Marit Dahl; White, Sarah; Chadban, S; Jenssen, Trond Geir (BMC Cardiovascular Disorders, 2013)
Background: The role of serum uric acid as an independent predictor of cardiovascular disease and death is uncertain in the general population. Adjustments for additional cardiovascular risk factors have not been consistent. We examined the association of serum uric acid with all-cause mortality, ischemic stroke and myocardial infarction in a prospective population based study, with several traditional and non-traditional risk factors for cardiovascular disease included in the model. Methods: A population-based prospective cohort study was performed among 2696 men and 3004 women. Endpoints were all-cause mortality after 15 years, and fatal or non-fatal myocardial infarction (MI) and ischemic stroke after 12 years. Results: 1433 deaths, 659 MIs and 430 ischemic strokes occurred during follow-up. Fully adjusted Cox regression analyses showed that per 1 SD (87 μmol/L) increase in serum uric acid level, the risk of all-cause mortality increased in both genders (hazard ratios, HR men; 1.11, 95% CI 1.02-1.20, women; 1.16, 1.05-1.29). HRs and 95% CI for stroke were 1.31, 1.14-1.50 in men, 1.13, 0.94-1.36 in women, and 1.22 (1.09, 1.35) in the overall population. No independent associations were observed with MI. Conclusion: Serum uric acid was associated with all-cause mortality in men and women, even after adjustment for blood pressure, estimated GFR, urinary albumin/creatinine ratio, drug intake and traditional cardiovascular risk factors. After the same adjustments, serum uric acid was associated with 31% increased risk of stroke in men.